Para-Social Relationship Activity: Case Study in Treasure and Treasure Maker on The Weverse App on 2023-2024 - Az Zahro, Amar Ma'ruf Syifa; Rochimah, Tri Hastuti Nur (Universitas Muhammdiyah Yogyakarta, 2025)
In recent years, the entertainment industry has witnessed growth driven by technological advancements and innovative applications of social media. Among these developments, the rise of social media platforms like Weverse has revolutionized how fans and idols engage with each other. Treasure, a K-Pop group, and its fandom, Treasure Maker, utilize Weverse to foster para-social relationships that enable fans to perceive an emotional connection with their idols despite physical separation. This study aims to explain the interaction between fans and idols in the Weverse app. The theoretical framework for this study is based on foundational theories relating to para-social relationships, including Horton and Wohl's conceptualization of media figures influencing audience behavior and Stever's classification of three types of para-social interactions: task attraction, identification attraction, and romantic attraction. Using a qualitative descriptive case study approach, the researcher seeks to understand the para-social activities facilitated by the features in the Weverse app. This research shows that the presence of digital platforms such as Weverse is able to strengthen the para-social relationship between Treasure and its fans. All the interactions that occur have made fans feel emotional closeness, which also fosters loyalty as fans towards their idols.